2018
DOI: 10.1038/s41467-018-04483-3
|View full text |Cite
|
Sign up to set email alerts
|

Observation of different reactivities of para and ortho-water towards trapped diazenylium ions

Abstract: Water is one of the most fundamental molecules in chemistry, biology and astrophysics. It exists as two distinct nuclear-spin isomers, para- and ortho-water, which do not interconvert in isolated molecules. The experimental challenges in preparing pure samples of the two isomers have thus far precluded a characterization of their individual chemical behavior. Capitalizing on recent advances in the electrostatic deflection of polar molecules, we separate the ground states of para- and ortho-water in a molecular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 33 publications
3
109
0
1
Order By: Relevance
“…They measured a twofold larger rate constant for a more polar conformer as a consequence of conformer-specific differences in the long-range ion-molecule interaction potentials (different leading long-range electrostatic coefficients C elst 2,1 for conformers with different dipole moments). In a similar experiment, (Kilaj et al, 2018) observed different reactivities of H 2 O molecules in para and ortho states in collisions with trapped diazenylium ions.…”
Section: E Cold Chemistrymentioning
confidence: 76%
See 1 more Smart Citation
“…They measured a twofold larger rate constant for a more polar conformer as a consequence of conformer-specific differences in the long-range ion-molecule interaction potentials (different leading long-range electrostatic coefficients C elst 2,1 for conformers with different dipole moments). In a similar experiment, (Kilaj et al, 2018) observed different reactivities of H 2 O molecules in para and ortho states in collisions with trapped diazenylium ions.…”
Section: E Cold Chemistrymentioning
confidence: 76%
“…These discoveries were followed by the first observation of Bose-Einstein condensation in dilute atomic gases in 1995 to Eric A. Cornell, Wolfgang Ketterle and Carl E. Wieman (Cornell and Wieman, 2002;Ketterle, 2002).…”
Section: Contentsmentioning
confidence: 98%
“…The present work suggests that rotations can play an important role for reactions involving large excess of translational energy and the implications for reaction dynamics involving polyatomic molecules are exciting. [55][56][57][58][59] As a next step, we intend to perform reactive molecular dynamics simulations for the cationic reaction between DBB and MA that is expected to be faster and in which concerted and stepwise mechanisms are anticipated to coexist. 23 To the best of our knowledge, no simulation study had been performed in Diels-Alder reactions starting from the beginning of the reaction without steered dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by trapping multiple ions together one can form spatially well defined ordered structures called Coulomb crystals. In these systems, molecular ions can be sympathetically cooled [27], and high-precision spectroscopic measurements [28] and controlled chemical reactions [29,30] can be performed. Even a heat engine using a single trapped ion was recently demonstrated [31].…”
Section: Introductionmentioning
confidence: 99%